Identification of the endangered species Haplotropis brunneriana (Insecta: Orthoptera) from South Korea using exuviae - Mannyun Kim; Hye-Rin Lee; Jong Eun Lee; Deokjea Cha (Journal of Insect Conservation, 2024)
Most Pamphagidae species are at risk of being endangered due to their flightlessness, low mobility, and small habitat range. For the same reason, Haplotropis brunneriana (Orthoptera: Pamphagidae) has been designated an endangered species in South Korea. Endangered species with small populations are difficult to observe and investigate because any damage or disturbance to them are prohibited. To address these problems, we first performed non-invasive genomic DNA (gDNA) extraction using exuviae to identify H. brunneriana . Second, we tested the limit of detection of gDNA in the exuviae and how long it could persist when exposed to artificial environmental conditions. Using exuviae, we identified cytochrome b as a species-specific marker of H . brunneriana that could distinguish them from other grasshoppers with sufficient specificity. In the limit of detection test, gDNA could persist and be amplified from exuviae for up to 40 days. Our results demonstrated that fewer than 10 days is recommended for amplifying gDNA from exuviae to obtain reproducible results. In conclusion, this non-invasive identification method using exuviae can be used as an alternative to species identification when it is difficult to find H. brunneriana in the habitat and has the advantage of allowing genetic research to be conducted without harming the endangered species.